Application and prospects of three-dimensional modelling technology in rectal cancer surgery - CHEN Zilong, ZHAO Ren (Waike lilun yu shijian)
Surgery is the mainly treatment for rectal cancer. Rectal cancer surgery currently poses specific challenges due to the complex anatomy of pelvic and narrow operating area. Three-dimensional(3D) modelling transforms two-dimensional images into three-dimensional models, makes medical imaging more intuitive and closer to the real surgical procedure. 3D modelling can reconstruct lesions along with surrounding structures, such as organs, vessels, and nerves, thereby enhancing disease diagnosis and treatment. Currently, 3D modelling technology has played a significant role in preoperative planning, intraoperative navigation, medical education, and other fields in orthopedics, urology, thoracic surgery and other surgery. However, its application in rectal surgery is still in the exploratory stage. This article provided a review of the relevant research and progress of 3D modelling in rectal cancer surgery, to improve the development of this technology.